2020
DOI: 10.1108/cr-01-2020-0021
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the effects of human capital composition, innovation portfolio and size on manufacturing firm performance

Abstract: Purpose This paper aims to focus on the effects of human capital composition, innovation portfolio and size on manufacturing firms’ performance. Moreover, it seeks to empirically identify the levels of education that are significant in labour productivity. Design/methodology/approach The resource-based view (RBV) theory is applied using data gathered from the National Innovation Survey in the Manufacturing Industries of Peru. Using the ordinary least squares method on a sample of 584 Peruvian manufacturing f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 74 publications
4
26
0
1
Order By: Relevance
“…Therefore, it can be stated that these results support the hypotheses (H4a). In particular, we can affirm that product-service innovation has a positive effect on the productivity of large manufacturing companies, as found in previous studies [76,91].…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Therefore, it can be stated that these results support the hypotheses (H4a). In particular, we can affirm that product-service innovation has a positive effect on the productivity of large manufacturing companies, as found in previous studies [76,91].…”
Section: Resultssupporting
confidence: 90%
“…Thus, the firms with less than 50 employees focus their efforts on increasing productivity while companies with more than 50 employees divide their efforts between productivity and environmental impact. Possibly the "productive muscle" of large companies also makes it possible to focus efforts on caring for the environment, as has been mentioned by previous studies [76,91]. In any case, our empirical evidence shows us that even though very few companies carry out product-service innovation, they obtain greater positive effects on productivity and the environment, especially in large companies.…”
Section: Theoretical Implicationssupporting
confidence: 66%
See 1 more Smart Citation
“…That is, domestic educational system and shape increases with the level of human capital in effectively educated countries. Seclen-Luna et al (2020) explored the effects of human capital composition on manufacturing firm performance. The results found that there is a positive relationship between human capital composition, workers' education level, and labor productivity in manufacturing firms.…”
Section: Education Level As Human Capitalmentioning
confidence: 99%
“…The reason is that firms can understand customers' long-term needs, expectation and preference [23]. The collaboration is similar to product-service innovation in an innovation portfolio [24]. Therefore, firms that want to achieve customer needs through the collaboration need to focus on internal collaboration, attain customer needs through collaboration with suppliers, and respond to customer expectation very well [25].…”
Section: Literature Reviewmentioning
confidence: 99%